A Coupled Euler-Lagrange Model for More Realistic Simulation of Debris Denting in Rolling Element Bearings. Issue 5 (3rd September 2019) - Bonetto, Alexis; Nélias, Daniel; Chaise, Thibaut; Zamponi, Laurent
Abstract: The objective of this study is to investigate the effects of the contamination of lubricants on denting in rolling element bearings. A dynamic, explicit finite element model (FEM) is developed to reproduce and analyse the elastic–plastic response of the surfaces when a spherical particle passes through a heavily loaded contact area. To cope with mesh distortion issues due to the high deformation of the debris along the process, a novel Eulerian approach is used to model the particle. A parametric study is conducted with the coupled Euler-Lagrange (CEL) model to determine the influence of the debris size, bearing loading, friction coefficient, material properties, and relative sliding between the surfaces on the indentation features. The FEM results emphasize the major role of the material properties of the three bodies on the dent geometry, pointing out that the softer surface undergoes more severe damage. In the same way, the protection of one of the surfaces by a specific heat treatment such as nitriding leads to more severe damage on the other one. The results exhibit a direct link between the particle and dent sizes. For large particles, a change in the dent geometry is observed when the deformed particle size overcomes the contact width because the particle is no longer enclosed in the contact and is therefore spread more easily. The model reproduces two important aspects of the indentation in rolling element bearings, which are the asymmetry of the dent and the residual stresses distribution, providing interesting prospects for future work on the fatigue failure caused by these defects.